Suctorians (Ciliophora: Suctoria) as epibionts of decapods of families Cambaridae and Pseudothelphusidae - Ramírez-Ballesteros, Mireya; Mayén-Estrada, Rosaura (Zootaxa, 2019)
Epibiosis is common among ciliates and crustaceans because the calcified surface of the crustacean body offers a suitable site for colonization by the epibiont. Suctoria are among the most common epibiont ciliate groups of freshwater decapod crustaceans. The aim of this study is to increase knowledge of suctorians as epibionts of freshwater decapod crustaceans of the families Cambaridae and Pseudothelphusidae. Crustaceans were collected from three rivers and one pond in Chiapas, Mexico. Six species of suctorian epibionts were recorded: Acineta tuberosa, Podophrya maupasi, P. sandi, Tokophrya cyclopum, T. quadripartita and Trichophrya epistylidis. This is the first record of ciliate epibionts on members of family Pseudothelphusidae (represented by Phrygiopilus montebelloensis and Raddaus bocourti), and the first record of suctorians epibionts on Procambarus (Austrocambarus) sp. (Cambaridae).